Method for optimization of frequency resource allocation with frequency reuse for cognitive radio system - Kolyadenko, Yu.Yu.; Kolyadenko, О.V.; Mulyar, B.P. (Radiotekhnika, 2021)
The concept of cognitive radio can be described as a radio with the study of capabilities, i.e. as a radio that is able to gain knowledge about the radio environment and adjust its operating parameters and protocols accordingly. The task of minimizing the frequency band is relevant at the stage of the cognitive radio network functioning when distributing the frequency resource between subscriber stations. With the ever-growing demand for frequency bands, this challenge is driven by the need to improve the efficient use of the radio frequency spectrum through frequency reuse methods. This paper proposes a method for ensuring the reuse of frequencies based on obtaining estimates of mutual distances between subscriber stations in real time. An algorithm is proposed for solving the problem of frequency resource allocation optimization for a cognitive radio network with frequency reuse. The algorithm is based on the method of local optimization, one of the approximate methods of discrete programming. In this case, the condition of local optimality is that the operating frequency assigned to the next subscriber station must be the closest to the frequency assigned in the previous step. The efficiency of the frequency resource optimization algorithm for the LTE network was analyzed using simulation modeling. The dependences of the bandwidth on the number of subscriber stations served are obtained. The analysis showed that the use of this algorithm allows to reduce the frequency band by 2 -3 times. The analysis also showed that the efficiency of the algorithm increases with the growth of the number of subscriber stations served simultaneously.